Adipose tissue (P)RR regulates insulin sensitivity, fat mass and body weight - Shamansurova, Zulaykho; Tan, Paul; Ahmed, Basma; Pepin, Emilie; Seda, Ondrej; Lavoie, Julie L (Molecular metabolism, 2016)
OBJECTIVE: We previously demonstrated that the handle-region peptide, a prorenin/renin receptor [(P)RR] blocker, reduces body weight and fat mass and may improve insulin sensitivity in high-fat fed mice. We hypothesized that knocking out the adipose tissue (P)RR gene would prevent weight gain and insulin resistance. METHODS: An adipose tissue-specific (P)RR knockout (KO) mouse was created by Cre-loxP technology using AP2-Cre recombinase mice. Because the (P)RR gene is located on the X chromosome, hemizygous males were complete KO and had a more pronounced phenotype on a normal diet (ND) diet compared to heterozygous KO females. Therefore, we challenged the female mice with a high-fat diet (HFD) to uncover certain phenotypes. Mice were maintained on either diet for 9 weeks. RESULTS: KO mice had lower body weights compared to wild-types (WT). Only hemizygous male KO mice presented with lower total fat mass, higher total lean mass as well as smaller adipocytes compared to WT mice. Although food intake was similar between genotypes, locomotor activity during the active period was increased in both male and female KO mice. Interestingly, only male KO mice had increased O2 consumption and CO2 production during the entire 24-hour period, suggesting an increased basal metabolic rate. Although glycemia during a glucose tolerance test was similar, KO males as well as HFD-fed females had lower plasma insulin and C-peptide levels compared to WT mice, suggesting improved insulin sensitivity. Remarkably, all KO animals exhibited higher circulating adiponectin levels, suggesting that this phenotype can occur even in the absence of a significant reduction in adipose tissue weight, as observed in females and, thus, may be a specific effect related to the (P)RR. CONCLUSIONS: (P)RR may be an important therapeutic target for the treatment of obesity and its associated complications such as type 2 diabetes.
Keywords: PGF, perigonadal fat; BB, beam break; RAS, renin-angiotensin system; PRA, plasma renin activity; VCO2, carbon dioxide production; Adipose tissue knock-out mice; PRF, perirenal fat; HFD, high-fat diet; TG, triglycerides; ND, normal diet; Insulin resistance; HACT, horizontal activity; BAT, brown adipose tissue; KO, knock-out; SFC, abdominal subcutaneous fat; SM, skeletal muscle; OGTT, oral glucose tolerance test; V-ATPase, vacuolar proton pump H+-ATPase; Renin-angiotensin system; PPAR-γ, peroxisome proliferator-activated receptor-γ; SE, standard error; (P)RR, prorenin/renin receptor; HRP, handle-region peptide; ANG, Angiotensin; WT, wild-type; Obesity; VO2, oxygen consumption; Adipose tissue; (Pro)renin receptor; SMG, submandibular gland